Actual problems of health of the economy of Kazakhstan: the transition to the concept of economy of public health. (Journal of Economic Research & Business Administration, 2015)
The basis of the formation of an effective strategy to promote health in Kazakhstan is the transition from the concept of health economics ( health care ) to the economy of public health that reflects a comprehensive approach to the problem of optimal allocation of scarce economic resources on priority areas of health of the population. The article deals with the analysis of modern concepts of health economics, public health models, as well as current problems of implementing the strategic directions of Kazakhstan's health system
Keywords: health economics; life expectancy; health; human development index